168k views
1 vote
What is the solution to -4 (2x +6)=-24

User P K
by
6.0k points

2 Answers

4 votes

Answer:

x=0

Explanation:

Step 1: Simplify both sides of the equation.

−4(2x+6)=−24

(−4)(2x)+(−4)(6)=−24(Distribute)

−8x+−24=−24

−8x−24=−24

Step 2: Add 24 to both sides.

−8x−24+24=−24+24

−8x=0

Step 3: Divide both sides by -8.

−8x

−8

=

0

−8

x=0

Answer:

x=0

User Rijo
by
6.2k points
5 votes

Answer:

x=0

Explanation:

Distribute -4

-8x - 24 = -24

Add 24 to both sides

-8x = 0

x=0

User Ilhnctn
by
5.8k points